Análisis de la actividad agrícola como contaminante del agua, alternativas tecnológicas para la desinfección del agua para consumo humano en comunidades rurales y recursos legislativos para la prevención y su conservación - Párraga, C. (2010)
The lack of treated water in rural communities is the main reason for diseases. The consumption of different chemical contained in water for years by this people causes intellectual deficiency, what becomes a main problem with the development of these communities. The Solar Cylindric-Parabolic Manifolds (CPC) is one of many models of photocatalytic reactors and they are considered the best choice for solar radiation based photocatalytic processes. By this, the design of CPC’s with steady catalyst adapts to the boundaries and needs of the rural communities concerning water disinfection. This means it is efficient, easy usable and low cost, due to very far distances from main cities or among them what makes hard to install electric or drinking water networks.